2016
DOI: 10.1007/s00234-016-1666-1
|View full text |Cite
|
Sign up to set email alerts
|

Curative embolization of pediatric intracranial arteriovenous malformations using Onyx: the role of new embolization techniques on patient outcomes

Abstract: Onyx embolization of AVM in pediatric patients with the intention to cure resulted in high occlusion rates without increasing neurological disability or death. The development of new embolization techniques and devices seems to improve the safety of Onyx embolization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
20
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 34 publications
2
20
1
2
Order By: Relevance
“…3,6 In this series, a greater propensity for multimodality treatment was evident, with nearly 80% of patients undergoing microsurgery or radiosurgery, compared with 9% in the 2014 report by Baharvahdat et al 3 Several studies that have recently reported high angiographic cure rates using Onyx embolization to treat intracranial AVMs have primarily been based on the use of detachable-tip microcatheters. 1,6,20,29,36 Comparatively, the results from the current study also appear to be congruent with reports from some of the largest published studies on Onyx embolization of brain AVMs (Table 4). 10,11,14,17,19,21,23,[25][26][27][28]30,32,35,[37][38][39][40]…”
Section: Discussionmentioning
confidence: 76%
“…3,6 In this series, a greater propensity for multimodality treatment was evident, with nearly 80% of patients undergoing microsurgery or radiosurgery, compared with 9% in the 2014 report by Baharvahdat et al 3 Several studies that have recently reported high angiographic cure rates using Onyx embolization to treat intracranial AVMs have primarily been based on the use of detachable-tip microcatheters. 1,6,20,29,36 Comparatively, the results from the current study also appear to be congruent with reports from some of the largest published studies on Onyx embolization of brain AVMs (Table 4). 10,11,14,17,19,21,23,[25][26][27][28]30,32,35,[37][38][39][40]…”
Section: Discussionmentioning
confidence: 76%
“…It was not clear how much of the poor outcome was related to surgical resection, embolization, or delayed hemorrhage from partially embolized AVM. On the other hand, a curative embolization with Onyx with high cure rates as recently published (van Rooij et al 2012 ; de Castro-Afonso et al 2016 ) that was associated with low morbidity and mortality (< 10%) may serve as a good treatment option. A low complication rate (< 10%) is lower than the complication rate of the medical arm of the ARUBA trial (Mohr et al 2014 ).…”
Section: Discussionmentioning
confidence: 92%
“…In the current study, complete occlusion was achieved in 9 patients (42.9%), this cure rate is similar to the previously quieted figures, and this high cure rate could be explained by the prior intention to completely occlude the lesion whenever possible, the use of Oynx with detachable tip catheters which permit longer injection time, and the use of staged approach. With case selection, van Rooij et al ( 2012 ) reported achievement of cure for all the selected patient (24 patients) using Onyx without morbidity or mortality; also, de Castro-Afonso et al ( 2016 ) reported (91.3%) cure rate in their selected AVM pediatric patients (23 patients) with (13%, 3 patients) procedure-related complications, yet without significant morbidity or mortality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a sole modality, neurointervention in pediatric populations achieves a high cure rate ranging from 84% to 95% in recent literature 11 10. It is also used as a part of multimodal treatment, in combination with radiosurgery or surgery with high cure rates 12–16.…”
Section: Discussionmentioning
confidence: 99%